An easy assembled fluorescent sensor for dicarboxylates and acidic amino acids - Zhou, Xiao-bo; Yip, Yuk-Wang; Chan, Wing-Hong; Lee, Albert W. M. (Beilstein Journal of Organic Chemistry, 2011)
Two mesitylene based neutral receptors 1 and 2 bearing two thiourea binding sites were constructed as fluorescent probes for sensing dicarboxylates. Their binding affinities toward dicarboxylates, aspartate and glutamate have been investigated in acetonitrile solution by fluorescence titration experiments. Both fluorescent sensors exhibited some ability to discriminate the antipodal forms of aspartate and glutamate.
Keywords: amino acids; dicarboxylate ion recognition; enantioselectivity; mesitylene scaffold